Microbiomes of Tilapia Culture Systems: Composition, Affecting Factors, and Future Perspectives - Huavas, Jonabel; Heyse, Jasmine; Props, Ruben; Delamare-Deboutteville, Jerome; Shelley, Colin (Wiley, 2024)
With the increasing demand for global food resources, improving aquaculture production has been the focus for years. Tilapia has become one of the most commonly farmed and economically important fish species globally. Research efforts have recognized the significant roles that microbial communities play in improving the health and aquaculture performance of tilapia. However, interactions between tilapia and its associated microbial communities remain poorly understood. In this review, the current understanding of tilapia microbiomes is summarized. With fish being in intimate relationship with its environment, studies characterizing the microbial communities present in the rearing environment and how they affect tilapia microbiomes and health are also examined. Having an in-depth understanding of the different microbiomes and their roles and interactions in the tilapia culture system is a crucial step toward managing and modulating these microbial communities to improve tilapia health. This review also sheds light on the different factors that influence tilapia microbiomes such as developmental stages, organ tissues, and types of culture systems. The effects of on-farm practices such as diet; feeding regimes; use of probiotics, prebiotics, and synbiotics; vaccination; application of antibiotics; disinfection; and pond fertilization on tilapia microbiome are also discussed. Through this review, future research needs are identified that can provide a deeper understanding of the relationships among tilapia microbiomes, health, and productivity. These knowledge in turn can be harnessed into practical applications and potential microbiome-based management protocols to improve future best management practices for tilapia aquaculture.